O ambiente institucional na viticultura do município de Jales-SP - da Silva, Gercina Gonçalves; Tredezini, Cícero Antônio de Oliveira; Andrade, Elisabeth de Souza; Cordeiro, Kelly Wolff (Universidade Federal Rural do Rio de Janeiro, 2015)
The production process of table grape in the Northwest region of São Paulo began in the 60s and today presents itself as an activity of big importance, this activity is an alternative of work and income generation for small scale producers. The city of Jales is considered the larg est producer of table grapes in the region. The objective of this study is to describe the institutional environment present in the production of table grapes from Jales-SP, based on studies of the New Institutional Economics. To meet the proposed bjectives, primary and secondary data were used, as well as semi-structured interviews with the most important institutional actors in the region and with the producers of local viticulture. It was found the existence of a fragile institution al environment by not stimulating the continuity of culture, This could be done through policies directed specifically to the viticulture, such as, for example, a line of credit that responds to the producers demand. Other attitudes could motivate the continued and increased investment in culture, for example the institutional agent to coordinate the activities, promoting the product, generating confidence in institutional actors, thro ugh greater involvement and coordination among them.